Sistem Pengkaderan Pendidikan Tinggi Kader Ulama (PTKU) Majelis Ulama Indonesia Sumatra Utara - Hidayana, Rika; Salminawati, Salminawati; Dahlan, Zaini (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to describe the cadre system of Higher Education Ulema Cadres (PTKU) of the Indonesian Ulema Council (MUI) North Sumatera. This research is qualitative and has a case study type. Research data is in the form of a cadre system at PTKU, with data sources from stakeholders who play a role and related documentation. Observation, interviews, and documentation carry out data collection techniques. The data analysis is carried out by reducing data, presenting data, and drawing conclusions. The study's results said that efforts to form the character of qualified scholars with the main focus on Sharia science had been carried out by PTKU, namely by carrying out discipline and regulating scientific structures. PTKU MUI North Sumatera also emphasizes strict rules and curriculum, creating discipline and a conducive learning environment. In addition, the emphasis on extra-curricular activities such as memorizing the Quran and batik training aims to improve students' skills and religion. The conclusion of this study highlights the effectiveness of PTKU's holistic approach in shaping the character of scholars who can meet the demands of the times